A novel approach in non-surgical management of tubal ectopic: combination of minimally invasive technique under ultrasound guidance with systemic methotrexate based on initial beta-HCG levels - Chakraborty, Mayoukh Kumar; Gainder, Shalini; Saha, Subhas Chandra; Bagga, Rashmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Single dose methotrexate is the most preferred method of non-surgical management of unruptured tubal ectopic. A 2-dose regimen is suggested to treat tubal ectopic with higher trophoblastic cell load. Minimally invasive technique of ultrasound guided intracardiac KCL instillation along with systemic methotrexate has been in use even for live ectopic pregnancy. Objective of the study was to evaluate the success rate of single dose regimen of MTX (Methotrexate), 2-dose regimen of MTX and ultrasound guided instillation of intracardiac KCl in three different cohort of unruptured tubal ectopic pregnancy with an attempt to increase success of non-surgical management. Methods: Fifty-eight women with unruptured tubal ectopic pregnancy were assigned to treatment protocols according to the initial β-HCG levels and presence/absence of FCA (fetal cardiac activity). Group 1: presence of FCA in the tubal ectopic; Group 2: initial β-HCG ≤5000 IU/ml; Group 3: initial β-HCG ≥5000 IU/ml without FCA. Women in group 1 were treated with ultrasound guided instillation of intracardiac KCl combined with systemic MTX. While women in group 2 were administered single dose regimen of MTX and group 3 received 2-dose regimen of MTX. Results: Overall success rate of non-surgical management was 89.3% across all groups. Success rate in Group 1 was 78.6%. Success rate was 93.1% in group 2 while 92.3% in group 3. Rupture rate was 1.7% in the present study. Conclusions: For non-surgical management categorizing and treating is an option with good result. Women with presence of cardiac activity can opt for non-surgical option with likely resolution in 78% cases.